2000
DOI: 10.1007/s100960000409
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Septicemia with Pediococcus acidilactici After Long-Term Antibiotic Treatment

Abstract: Presented here is a case of septicemia caused by an uncommon, multiresistant, gram-positive microorganism (Pediococcus acidilactici) after long-term antibiotic treatment. Pediococcus spp. are rarely cultivated from clinical specimens, and species differentiation is difficult due to the paucity of phenotypic traits. In this case, a polyphasic approach consisting of phenotypic and molecular genetic analyses was used, and the identification of Pediococcus acidilactici was conclusive. Precise identification and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Our case represents only the second time that daptomycin was successfully used in therapy and the first time this drug was used to treat a confirmed case of endocarditis (10). Finally, this present case is only the second time that molecular sequencing was performed to verify the species identification (6). Most of the previous cases used a series of biochemical tests to provide a species identification.…”
Section: Case Reportmentioning
confidence: 76%
See 1 more Smart Citation
“…Our case represents only the second time that daptomycin was successfully used in therapy and the first time this drug was used to treat a confirmed case of endocarditis (10). Finally, this present case is only the second time that molecular sequencing was performed to verify the species identification (6). Most of the previous cases used a series of biochemical tests to provide a species identification.…”
Section: Case Reportmentioning
confidence: 76%
“…To overcome this, molecular sequencing has been considered (6). Heinz et al sequenced both the full-length 16S rRNA gene and the D-lactate dehydrogenase gene and was able to show a 99% similarity to the P. acidilactici type strain (DSM 20284) in the GenBank database, with the next closest identification to the P. pentosaceus type strain at 72.7% (6). We sequenced the intergenic spacer (IGS) region target within the rRNA gene complex, which also was able to give reliable results using comparison analysis in the GenBank database.…”
Section: Case Reportmentioning
confidence: 99%
“…2,15 Underlying diseases and conditions associated with Pediococcus infection include chronic lung disease, 14 gastroschisis, 11 congenital jejunoileal atresia, 13 inflammatory bowel disease, 2 diabetes, 2 hematologic malignancies, 12 neutropenic patients, 16 previous abdominal surgeries, 2 presence of central venous access for total parenteral nutrition, 16 and long-term antibiotic use. 10 Some of these reports have described delays in the identification of this pathogen and the persistence of symptoms while receiving vancomycin. 10,12 Pediococcus acidilactici has been the most common isolate recovered 1,11 and has been significantly associated with bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…10 Some of these reports have described delays in the identification of this pathogen and the persistence of symptoms while receiving vancomycin. 10,12 Pediococcus acidilactici has been the most common isolate recovered 1,11 and has been significantly associated with bacteremia. 4 Pediococcus parvulus has not been previously reported as a cause of infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A 1,002-bp ORF that potentially encodes a 334-amino-acid protein was identified as DLDH. BLAST searches revealed that the nucleotide and deduced amino acid sequences for this ORF have identities of 78 to 90% and 43 to 62%, respectively, to the sequences of published DLDH enzymes from other lactic acid bacteria (LAB) (3,4,10,12,14,15,16,17) (Fig. 2) , and Streptococcus thermophilus LMD-9).…”
mentioning
confidence: 89%